Nutritional status, the development and persistence of malnutrition and dietary intake in oesophago‐gastric cancer: a longitudinal cohort study. Issue 6 (22nd July 2018) - Grace, E. M.; Shaw, C.; Lalji, A.; Mohammed, K.; Andreyev, H. J. N.; Whelan, K.
Abstract: Background: Patients with oesophago‐gastric (OG) cancer may be at risk of malnutrition, troublesome gastrointestinal symptoms (GI) and reduced dietary intake in view of the tumour location and multimodality curative treatment approach. Longitudinal research is lacking. The present study aimed to assess (i) nutritional status and how it evolved over the first year; (ii) the association between nutritional status scores and GI symptom scores; and (iii) the nutrient and food group intake pattern. Methods: This was a prospective, observational study of patients with an OG lesion planned for radical treatment, with assessment at diagnosis, 3 months and 12 months after the start of treatment. Nutritional assessment was performed using the Patient‐Generated Subjective Global Assessment, GI symptoms measured using the modified Gastrointestinal Symptom Rating Scale and dietary intake assessed using a semi‐quantitative food frequency approach. Results: Eighty patients (61 males, 19 females; aged 46–89 years) were recruited. At baseline, 3 ( n  =   68) and 12 months ( n  =   57), 61%, 62% and 60%, respectively, were moderately/severely malnourished. Higher symptom burden was associated with poorer nutritional status at baseline ( r  =   0.55, P  <   0.001), 3 months ( r  =   0.51, P  <   0.001) and 12 months ( r  =   0.42, P  =   0.001). At each respective time point, 37%, 38% and 42% were meeting their estimated average requirement for energy. No change in mean (SD) intake of energy, fibre, nutrient and food groups was observed over time. Conclusions: Patients with OG cancer have progressive weight loss, with malnutrition present over the majority of the 12‐month study period. Optimising nutritional status and symptom management throughout the treatment pathway should be a clinical priority.